KEANEKARAGAMAN JENIS KEPITING BAKAU DI KAWASAN HUTAN MANGROVE DESA KERAMAT JAYA KECAMATAN KENDAWANGAN KABUPATEN KETAPANG - Damiska, Septi; Putra, Diki Heryanto; Darwati, Herlina; Dewantara, Iswan (Tengkawang : Jurnal Ilmu Kehutanan, 2024)
Scylla spp is a fishery commodity that has the potential to support community life, especially for small-scale fishermen. The mangrove ecosystem has an important role as the main habitat for mangrove crabs (Scylla Spp). The mangrove ecosystem (mangrove) is an ecosystem located in coastal areas that is influenced by sea tides so that the floor is always flooded with water. The aim of research on the diversity of mangrove crabs (Scylla spp) in the mangrove ecosystem is to record and describe the types of mangrove crabs (Scylla spp) in the mangrove vegetation and surrounding areas in the mangrove forests of Keramat Jaya Village, Kendawangan District, Ketapang Regency. Data was collected from various sources including the types, numbers and populations of mud crabs found at the research location. The data taken is primary data and secondary data. The data obtained was then analyzed, namely the species diversity index (H'), number of individuals (ni), total number of individuals (n), species abundance (N) and analysis of habitat conditions. The research results obtained 3 species from 3 locations with a total of 30 individuals. The value of the species diversity index H'=1,0692, the value of the number of individuals ni=0,33, the value of the total number of individuals n=1,108 and the value of species abundance N=0,3564. Scylla olivacea has the highest number of individuals, namely 11 individuals, while the lowest number of individuals is Scylla serrata, 9 individuals.Keywords: Ecotourism, Kendawangan, Mangrove, Scylla sppAbstrakKepiting bakau merupakan salah satu komoditas perikanan yang memiliki potensi sebagai penyangga kehidupan masyarakat terutama bagi nelayan sekala kecil. Ekosistem mangrove mempunyai peran penting sebagai habitat utama bagi kepiting bakau (Scylla Spp). Ekosistem mangrove (bakau) adalah ekosistem yang berada di daerah tepi pantai yang dipengaruhi oleh pasang surut air laut sehingga lantainya selalu tergenang air. Penelitian ini bertujuan untuk mendata dan mendeskripsikan jenis kepiting bakau (Scylla spp) pada vegetasi bakau dan sekitarnya di hutan mangrove Desa Keramat Jaya Kecamatan Kendawangan Kabupaten Ketapang. Pengumpulan data di lakukan dari berbagai sumber yang meliputi jenis-jenis, jumlah dan populasi kepiting bakau yang ditemukan di lokasi penelitian. Data yang diambil berupa data primer dan data sekunder yang kemudian dianalisis, yaitu Indeks keanekaragaman jenis (H"™), Jumlah individu (ni), Jumlah total individu (n), Kelimpahan jenis (N) dan analisis kondisi habitat. Hasil penelitian diperoleh 3 jenis dari 3 lokasi dengan jumlah individu 30 ekor. Nilai indeks keanekaragaman jenis (H"™)=1,0692, nilai jumlah individu (ni)=0,33, nilai jumlah total individu (n)=1.108 dan nilai kelimpahan jenis (N)=0,3564. S. olivacea memiliki jumlah individu tertinggi yaitu 11 ekor sedangkan jumlah individu paling sedikit yaitu S. serrata 9 ekor.Kata kunci: Ekowisata, Kendawangan, Kepiting Bakau, Mangrove